Respiratory effects of exposure of shipyard workers to epoxy paints. Issue 11 (November 1991) - Rempel, D; Jones, J; Atterbury, M; Balmes, J
Abstract : Epoxy resin systems have been associated with occupational asthma in several case reports, but medical publications contain little on the potential adverse respiratory effects of these chemicals in exposed worker populations. To further evaluate the association of workplace exposure to epoxy paints and respiratory dysfunction, the cross workshift changes in pulmonary function and symptoms of 32 shipyard painters exposed to epoxy paints were compared with 28 shipyard painters not exposed to epoxy paints. The prevalence of lower respiratory tract symptoms was significantly higher among painters exposed to epoxy paints compared with controls. Among exposed painters the mean cross workshift change in forced expiratory volume in one second (FEV1) (-3.4%) was greater than the decrement in the non-exposed group (-1.4%). A significant linear relation was seen between % decrement in FEV1 and hours of exposure to epoxy paints. This study suggests that epoxy resin coatings as used by shipyard painters are associated with increased lower respiratory tract symptoms and acute decrements in FEV1. Adequate respiratory protection and medical surveillance programmes should be established in workplaces where exposure to epoxy resin systems occurs.